The use of epoxidised natural rubber latex for developing coloured adhesives / Rohani Abu Bakar and Asrul Mustafa - Abu Bakar, Rohani; Mustafa, Asrul (Universiti Teknologi MARA, Negeri Sembilan, 2020)
Adhesives serve many functions in daily life, starting from sticking envelopes to rejoining broken materials. Adhesives are usually developed for a specific purpose and the performances can vary according to their specific end-use. Most of the commercially available adhesives comprised non-renewable or petroleum derived raw materials. Thus, in order to mitigate negative impact of using non-renewable material as the raw material for adhesives, a new type of adhesive containing epoxidised natural rubber (NR) latex is developed. Epoxidised NR latex adhesive was initially prepared and pigment was subsequently added to produce desired colours of the adhesive. Hence, the newly developed adhesive can serve as adhesive and also as paint for art. The adhesives were characterised and the results indicated that they were free from heavy metal contents and volatile organic compounds (VOCs). The adhesives exhibited comparable odour concentration to commercial synthetic-based adhesive. In terms of toxicity level, the adhesive developed exhibited low acute oral toxicity. Peel adhesion test of A4 and drawing papers on stainless steel and glass substrates, opacity and glossiness were also investigated in the present study. This coloured adhesive is deemed to support the STEM (science, technology, engineering and mathematics) learning by indirectly imparting polymer science and technology in art education and further promotes creative learning among school children. The adhesive is also derived from renewable material rendering it more environmentally friendly.